Study on factors that drive employee retention in Syarikat Air Melaka Berhad (SAMB) / Alena Abu Bakar and Hasline Asan Gabra - Abu Bakar, Alena; Asan Gabra, Hasline (Faculty of Business and Management, 2015)
The purpose of this study is to investigate the relationship between three chosen factors; compensation and benefit, training and development, and relationship with others toward the employee retention among employees in SAMB. The overall population in SAMB is 710 employees. This study is using a sample of 169. The instrument used is a questionnaire, consisting of five sections and 54 items. The returned rate of questionnaire is only 110. Analysis of the survey showed a significant relationship between those three independent variables with employee retention. The findings of this study also indicates that the most influence factor among the three independent variables tested that affect employee retention is training and development.